Регіональні тенденції розвитку мережевої економіки. - Olena, Popadiuk; Кравчук, Ірина (My University, 2021)
Computerization in almost all regions of the world and the use of information and communication technologies has become an integral part in building economic relations between individual businesses and states as a whole.The transfer of various types of socio-economic activities to the electronic environment has led to the formation of a new form of economic relations - the network economy. Building and expanding the information society causes the necessity of determining Ukraine's place in the global information space. It is also necessary to identify opportunities to increase competitiveness by using best practices in the use of ICT in all sectors of the economy. The aim of the article is to study the system of monitoring and evaluation of the ICT sector at the regional level to form areas of work in the field of network economy, aimed at overcoming "network inequality" between Ukraine and its international competitors. Methodology. Theoretical and methodological basis of scientific work are general scientific principles, methods, provisions, highlighted in the works of scientists who study the systems of monitoring and evaluation of the ICT sector at the regional level. Results. The article evaluates the development of the information and communication technology sector at the regional level to form areas of work in the field of network economy and identify ways to overcome "network inequality" between Ukraine and its international competitors. According to the analysis of the level of development of the network economy according to the ICT Development Index (IDI), the construction of the information society is aimed at forming an innovative model of development that will allow everyone to realize their potential for personal and social development and quality of life. To achieve this goal, it is necessary to: conduct effective public policy; participation of all regions in the processes of formation of the information society through decentralization and support of regional and local initiatives; development of the national information infrastructure and its integration with the world infrastructure. The practical meaning of the obtained results consists of the level of methodological and practical recommendations of the usage of a system of indicators and indices for assessing the development of national information infrastructure, which will encourage the growth of network economy and overall progress by a transformation of countries to the information society. Prospects for further research. This topic has the prospect of research in the direction of improving the methodological support for assessing network readiness and finding ways to overcome "network inequality" at the regional level.
Keywords: мережева економіка; регіональний розвиток; інформаційне суспільство; індекс цифрової спроможності; інформатизація; інформаційно-комунікаційні технології